The Effect of Dutch Student Errors in German Business Letters on German Professionals. Issue 1 (March 2020) - Luijkx, Antoinette; Gerritsen, Marinel; van Mulken, Margot
Two studies investigated the effects of errors in German business letters written by Dutch students. Gaining insight into these effects is important since Germany and the Netherlands are one of the largest economically interdependent partnerships. One hundred and fifty-six German professionals rated letters with errors and letters without errors on comprehensibility, attitude toward text, writer organization, and behavioral intention. Errors negatively affected attitude toward text, writer, and organization. The second study investigated whether pragmatic, syntactical, lexical, and morphological errors elicited different effects on the same variables. Pragmatic and syntactical errors aroused negative effects and, therefore, deserve extra attention in class.